Listening for the Norm: Adaptive Coding in Speech Categorization - Huang, Jingyuan; Holt, Lori L. (Frontiers in Psychology, 2012)
Perceptual aftereffects have been referred to as “the psychologist’s microelectrode” because they can expose dimensions of representation through the residual effect of a context stimulus upon perception of a subsequent target. The present study uses such context dependence to examine the dimensions of representation involved in a classic demonstration of “talker normalization” in speech perception. Whereas most accounts of talker normalization have emphasized talker-, speech- or articulatory-specific dimensions’ significance, the present work tests an alternative hypothesis: that the long-term average spectrum of speech context is responsible for patterns of context-dependent perception considered to be evidence for talker normalization. In support of this hypothesis, listeners’ vowel categorization was equivalently influenced by speech contexts manipulated to sound as though they were spoken by different talkers and nonspeech analogs matched in LTAS to the speech contexts. Since the nonspeech contexts did not possess talker, speech or articulatory information, general perceptual mechanisms are implicated. Results are described in terms of adaptive perceptual coding.